Bone healing during electrostimulation - Yurii Bezsmertnyi; Viktor Shevchuk; Yankai Jiang; Olena Shevchuk (Medicinski glasnik, 2023)
Aim: To investigate the effect of direct epineural electrical stimulation of the nerve on the nature of reparative processes in the bone stump. Methods: Three series of experiments were carried out with amputation of the thigh in the middle third and muscle plasty. In the 1st and 2nd experimental series a perineural catheter was brought to the stump of the sciatic nerve, through which mechanical irritation of the nerve was performed for 20 days daily for 20 minutes. In the 2nd series, an electrode was added to the nerve and epineural electrical stimulation was performed daily for 20 days. Animals of the 3rd series served as control. The observation periods were 1, 3, 6 months. Histological research method with filling vessels with ink-gelatin mixture was applied. Results: In the 1st series, there was a sharp distortion of the reparative process, which consisted of a violation of microcirculation, changes in shape, resorption of the cortical diaphyseal plate, fractures, deformations. In most experiments of the 2nd series, organotypic stumps were formed with normalization of microcirculation. In the 3rd series, results of the formation of the stump were better than in the 1st, but worse than in the 2nd series. Conclusions: Painful nerve irritation after amputation leads to a significant disturbance of microcirculation and reparative regeneration at the end of the bone stump with the development of pathological restructuring of bone tissue. Electrostimulation of the nerve improves microcirculation and reparative regeneration of the bone tissue.
Keywords: amputation; bone regeneration; epineural stimulation; microcirculation